A cell–cell atlas approach for understanding symbiotic interactions between microbes. (December 2021) - Alacid, Elisabet; Richards, Thomas A
Highlights: Microbial symbiotic interactions shape natural environments. The functional nature of most microbial symbiotic associations is unknown. Single-cell methods allow isolation and functional profiling of individual cells. Atlas approaches with imaging allow the basis of interactions to be quantized. Abstract : Natural environments are composed of a huge diversity of microorganisms interacting with each other to form complex functional networks. Our understanding of the operative nature of host–symbiont associations is limited because propagating such associations in a laboratory is challenging. The advent of single-cell technologies applied to, for example, animal cells and apicomplexan parasites has revolutionized our understanding of development and disease. Such cell atlas approaches generate maps of cell-specific processes and variations within cellular populations. These methods can now be combined with cellular-imaging so that interaction stage versus transcriptome state can be quantized for microbe-microbe interactions. We predict that the combination of these methods applied to the study of symbioses will transform our understanding of many ecological interactions, including those sampled directly from natural environments.